COVID‐19 outcomes in patients with cancer: Findings from the University of California health system database. (9th March 2022) - Kwon, Daniel H.; Cadena, Jose; Nguyen, Sam; Chan, Kwan Ho Ryan; Soper, Braden; Gryshuk, Amy L.; Hong, Julian C.; Ray, Priyadip; Huang, Franklin W.
Abstract: Background: The interaction between cancer diagnoses and COVID‐19 infection and outcomes is unclear. We leveraged a state‐wide, multi‐institutional database to assess cancer‐related risk factors for poor COVID‐19 outcomes. Methods: We conducted a retrospective cohort study using the University of California Health COVID Research Dataset, which includes electronic health data of patients tested for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) at 17 California medical centers. We identified adults tested for SARS‐CoV‐2 from 2/1/2020–12/31/2020 and selected a cohort of patients with cancer. We obtained demographic, clinical, cancer type, and antineoplastic therapy data. The primary outcome was hospitalization within 30d after the first positive SARS‐CoV‐2 test. Secondary outcomes were SARS‐CoV‐2 positivity and severe COVID‐19 (intensive care, mechanical ventilation, or death within 30d after the first positive test). We used multivariable logistic regression to identify cancer‐related factors associated with outcomes. Results: We identified 409, 462 patients undergoing SARS‐CoV‐2 testing. Of 49, 918 patients with cancer, 1781 (3.6%) tested positive. Patients with cancer were less likely to test positive (RR 0.70, 95% CI: 0.67–0.74, p  < 0.001). Among the 1781 SARS‐CoV‐2‐positive patients with cancer, BCR/ABL‐negative myeloproliferative neoplasms (RR 2.15, 95% CI: 1.25–3.41, p  = 0.007), venetoclax (RR 2.96, 95% CI: 1.14–5.66, p  = 0.028), and methotrexate (RR 2.72, 95% CI: 1.10–5.19, p  = 0.032) were associated with greater hospitalization risk. Cancer and therapy types were not associated with severe COVID‐19. Conclusions: In this large, diverse cohort, cancer was associated with a decreased risk of SARS‐CoV‐2 positivity. Patients with BCR/ABL‐negative myeloproliferative neoplasm or receiving methotrexate or venetoclax may be at increased risk of hospitalization following SARS‐CoV‐2 infection. Mechanistic and comparative studies are needed to validate findings. Abstract : In a large dataset of patients who underwent SARS‐CoV‐2 testing across 17 California medical centers, we conducted multivariable analyses to evaluate cancer‐related risk factors for poor COVID‐19 outcomes. We found that patients with cancer had a lower risk of SARS‐CoV‐2 positivity than those without cancer. BCR/ABL‐negative myeloproliferative neoplasms, venetoclax use, and methotrexate use were associated with an increased risk of hospitalization after a COVID‐19 diagnosis.